2015
DOI: 10.1016/s0186-1042(15)72151-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de gestión logística para pequeñas y medianas empresas en México

Abstract: The market opening and the globalization of supply chains, demand a structural changes in which logistics has a strategic role. Nowadays, clients evaluate product quality, its value added and its availability in time and form, which implies a need to make the process efficient. Several experts have proposed some logistics management models to increase competitiveness in the market, but some of these models are too ambitious for small and medium sized enterprises (SMEs) due to their informal structure and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
23

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 3 publications
0
5
0
23
Order By: Relevance
“…With these results, the questionnaire was restructured and modifications were made to the proposed ISC model [46].…”
Section: Structuring and Validation Of The Measurement Instrumentmentioning
confidence: 99%
See 3 more Smart Citations
“…With these results, the questionnaire was restructured and modifications were made to the proposed ISC model [46].…”
Section: Structuring and Validation Of The Measurement Instrumentmentioning
confidence: 99%
“…Values greater than 0.6 in KMO and less than 0.05 in Bartlett justify performing a factor analysis [46]. Having analysed the results, it could be concluded that the factor analysis could be properly applied.…”
Section: Structuring and Validation Of The Measurement Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…A pesar de que la Pyme tiene importancia en el nivel internacional y nacional, en general, carece de una estructura formal en la mayoría de sus áreas [6], [7]. Debido a su tamaño y la escasez de recursos económicos es común que los empleados realicen varias actividades para muchas de las cuales no son especialistas; suele observarse que las mismas personas que dirigen sean quienes también ejecuten funciones de planeación financiera, producción, administración de personal y comercialización, entre otras [8].…”
Section: Introductionunclassified